AI in drug discovery: A wake-up call - Urbina, Fabio; Lentzos, Filippa; Invernizzi, Cédric; Ekins, Sean (Drug discovery today, 2023)
Following a proof-of-concept presentation on dual-use artificial intelligence (AI) in drug discovery by Collaborations Pharmaceuticals Inc. to the Swiss Federal Institute for NBC-Protection, we explored how a generative algorithm could develop the nerve agent VX and tens of thousands of analogs in a highly impactful Nature Machine Intelligence commentary. We not only laid out the experiment, but, with guidance from experts on arms control and dual-use, we called for more discussion around the general repurposing potential of AI in drug discovery. To continue that conversation, we now share further details on the experiment and place our experiences in the larger frame of other scientists who have similarly developed powerful technologies but without engaging with, or even truly understanding, the misuse potential and downstream consequences of the technologies. It is our sincere hope that our experiment may serve as an important wake-up call for users of generative AI.